La puchka como técnica y desarrollo de coordinación óculo-manual - Inga-Choque, Vilma (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the University for Andean Development (Huancavelica - Peru), whose objective was to describe the relationship between the "puchka" as a technique and manual eye development in preschool children, demonstrating as the "puchka" intervenes in the development of certain manual eye coordination exercises in the I.E.P of Initial "Corazón de Jesús" -Lircay (Peru). The "puchka" is a spinning technique. This technique, in its execution and application, allows developing hand-eye coordination in children. The performance of certain exercises and fine psychomotor movements involve the eyes, hands, fingers and other aspects in certain manual eye coordination exercises that serve to initiate pre-writing and instruct in cognitive development, abilities, skills and others. The "puchka" is an ancient art that the ancient Peruvians have passed from generation to generation, allowing them to make beautiful cloaks and other pieces of fascinating cultural expression. The study is applied type and descriptive level. The result showed that, through the use of the "puchka" as a technique, manual eye development in children was improved, as stated in the main hypothesis of the project. The results can be used by the teachers of the Educational Institutions of the initial level in the realization of their activities related to the development of the manual eye coordination, since it will also favor the development of writing, strokes, molding, painting. , etc. Another aspect that must be taken into account is that it helps improve preschool care, as it is a more appropriate technique, since it is part of our socio-cultural environment.